Study on the preparation of PLGA-based microparticles / Fauziah Ismail - Ismail, Fauziah (2007)
The purpose of the research is to study the preparation of drug delivery system using biodegradable polymer. The advantage of biodegradable polymer over other drug delivery system is that they are absorbable by the body thus leaving no trace. The material used in preparing the microparticulate system was PLGA or poly (lactic-co-glycolic) acid. PLGA-based microparticle was prepared using emulsion solvent extraction technique. The technique involves two different phases; organic phase and aqueous phase. The organic phase contains of dichloromethane (as solvent) and PLGA (a polymer). Meanwhile, aqueous phase contains distilled water and polyvinyl alcohol (as a stabilizing agent). In the study, we were focusing on the different parameters that affect the formation of microparticles. Three different parameters were considered; homogenizing speed, stabilizer concentration and temperature. The samples were prepared and analyzed using optical microscope, particle size analyzers and scanning electron microscope. It was determined that the particles size and size distribution were strongly correlated to the following parameters; homogenizing speed, stabilizer concentration and temperature. Surface morphology was strongly affected by temperature. The others two parameters doesn't significantly influence the surface morphology of microparticles.